Global Challenges: Engaging Undergraduates in Project-Based Learning Online - Gail Matthews-Denatale; Laurie Poklop; Rachel Plews; Mary English (Teaching & Learning Inquiry: The ISSOTL Journal, 2024)
In summer 2020, Northeastern University developed a fully online curricular pathway for incoming fall first-year undergraduate students who could not learn in residence. This pathway included 18 Global Challenge (GC) courses, each designed around project-based learning (PBL), grounded in a complex problem defined by Northeastern University research faculty, and based on the classes’ individual research agendas (e.g., social justice, health, the environment). The GC courses were designed to help students develop key intrapersonal and interpersonal skills as well as academic proficiencies. The GC development team conducted a systematic study of the courses during the first three semesters of their development and implementation. The investigation’s guiding question was, “To what extent, and in what ways, can learning experience design, online structure, and facilitation support PBL learning, teamwork, and a sense of connection among students in asynchronous courses?” Data sources included student surveys, instructor reflections, and course observations. Findings highlighted the importance of a learning experience design infrastructure to support PBL challenge development; that design supports for challenge development are necessary, but not sufficient, and an online course architecture that reinforces PBL also needs to be developed; that student attention to course resources needs to be scaffolded within the course and optimized for the online modality; and that a system for instructor mentoring in online PBL pedagogy is important to course success.